The Cost of Getting Tough on Crime: Isn‘t Prevention the Policy Answer? - Fournier-Ruggles, Lynn (The Journal of Public Policy, Administration, and Law, 2011)
Abstract: The need to keep Canadians safe with "get tough on crime" policies is not supported by statistical information on crime rates, which shows that crime has been declining over the past decade, or by Canadians’ perceptions of well-being and safety. This article provides an overview of crime statistics and discusses the difficulty of measuring the effectiveness of the criminal justice system on crime rates. The political considerations that dominate the Harper government’s spending priorities to tackle crime invest only a small proportion in crime prevention strategies. The author proposes that instead of a policy of "tackling crime," Canada needs to strengthen its policies for "preventing crime," with corresponding funding to build healthier and safer communities.